2013
DOI: 10.1051/0004-6361/201220903
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of surviving companion stars after type Ia supernova explosions in the WD+MS scenario

Abstract: Context. In the single-degenerate (SD) scenario of type Ia supernovae (SNe Ia) the non-degenerate companion star survives the supernova (SN) explosion and thus should be visible near the center of the SN remnant and may show some unusual features. Therefore, a promising approach to test progenitor models of SNe Ia is to search for the companion star in historical SN remnants. Aims. Here we present the results of three-dimensional (3D) hydrodynamics simulations of the interaction between the SN Ia blast wave an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 56 publications
2
68
0
Order By: Relevance
“…These expectations, that follow from simple angular-momentum conservation considerations, have been confirmed by numerical simulations (e.g. Pan et al 2012a;Liu et al 2013), though we note that none of the simulations in Pan et al (2012a) can explain the observed properties of Tycho G as none can fit the observed gravity (log g) and the observed rotational velocity simultaneously. Fig.…”
Section: Companion Radius and Rotational Velocitysupporting
confidence: 64%
“…These expectations, that follow from simple angular-momentum conservation considerations, have been confirmed by numerical simulations (e.g. Pan et al 2012a;Liu et al 2013), though we note that none of the simulations in Pan et al (2012a) can explain the observed properties of Tycho G as none can fit the observed gravity (log g) and the observed rotational velocity simultaneously. Fig.…”
Section: Companion Radius and Rotational Velocitysupporting
confidence: 64%
“…We expect that some small morphological differences, such as the post-impact density distribution of all removed companion material and SN ejecta, would be seen if the orbital motion of the companion star is included, but it should not affect the basic results presented in this work (see also Liu et al 2013b). …”
Section: Impact Velocity Of the Companion Starmentioning
confidence: 90%
“…Thus, stars in a cluster or a binary system can be kicked out by a perturbation of the system, for instance, such as in a threebody encounter or a supernova explosion (e.g., Hoogerwerf et al 2000;Perets 2009;Irrgang et al 2010;Zhang et al 2013). To be more specific, there are several possible formation scenarios for HVSs: (1) interaction of single stars with a central massive black hole (MBH); (2) tidal break-up of binary stars in the vicinity of a MBH; (3) three-body interactions involving single-star encounters with a binary or cluster of MBHs; (4) double detonation of SN Ia with a close system of a rapidly orbiting low-mass compact He star and a massive (∼1−1.2 M ) CO-white dwarf (Geier et al 2015); (5) single-degenerate SN type Ia consisting of a white dwarf and a main-sequence star (Liu et al 2013); (6) binary star disruption in dense interacting regions such as globular clusters or the Galactic bulge or disk; or (7) tidal disruption of dwarf galaxies in the Galaxy (Li et al 2015, and references therein). The last case would lead to old rapidly traveling stars.…”
Section: High-velocity Starsmentioning
confidence: 99%